P109 The Santé project: Attitude towards STI risk assessment, preferences for STI behavioural risk reduction interventions: Service Users Perspectives. (30th June 2016) - Roy, Anupama; King, Carina; Miners, Alec; Llewellyn, Carrie; Pollard, Alex; Gilson, Richard; Richardson, Daniel; Clark, Laura; Burns, Fiona; Rodgers, Alison; Bailey, Julia; Shahmanesh, Maryam
Abstract : Background/introduction: A variety of risk-reduction interventions may be suitable for sexual health clinic attendees. Aim(s)/objectives: In the SANTE project, we explored service users' (SU) perceptions of their STI risk, and experiences and preferences for risk reduction interventions. Methods: Semi-structured interviews were conducted with 15 young people (YP) (16–25 years) and 20 MSM (≥16 years) from two SH clinics. Data were analysed thematically. Based on these, a Discrete Choice Experiment (DCE) to quantitatively assess YP and MSM preferences for interventions was designed and conducted in three clinics (n = 371). Results: Most participants, despite presenting with symptoms or concerned about STIs, did not perceive themselves to be at risk. Most reported receiving SH promotion but felt access to accurate information was lacking. While short advert-like videos were acceptable, onscreen material in waiting rooms was deemed inappropriate by some SUs. Opinions on group sessions were mixed. 1:1 sessions were favoured, with talking therapies acceptable if needed. Privacy around mobile apps was a concern while online materials from a reputable source were acceptable. DCE results demonstrated preferences for 'talking interventions', while all interventions were generally preferred to 'nothing'. People strongly disliked peer-led interventions compared to others, and preferred 1:1 to group sessions. Latent class analysis identified three respondent groups, those that preferred talking (56%), email/text (29%) or nothing (15%). Discussion/conclusion: Young people and MSM welcome SH promotion offered through SH clinics. Triangulation demonstrated strong preferences for 1:1 talking interventions. Awareness of sexual risk was not commensurate with actual risk, suggesting that providers need to direct service users to appropriate interventions.